Determination of the Content of Phenolic Compounds and the Changes of Polyphenol Oxidase and Each Index during Browning of Phyllanthus emblica at Different Storage Temperatures. (31st July 2022) - Li, Rong; Guo, Shuang; Wu, Wenjun; Lin, Aihe; Xia, Zongxiao; Long, Xiaomei; Liu, Tao; Fan, Yuan; Chen, Zukun
Abstract : In order to further study the early browning of P. emblica marker and mechanism, it is necessary for us to measure the changes in the content of some substances to find quality markers during the browning process of P. emblica . So, we simulated the storage conditions under different temperatures, including 5°C, 25°C, and 35°C. And, the contents of some of its phenolic compounds were determined by RP-HPLC. Polyphenol oxidase (PPO) activity was determined by PPO reagent kits, and pH was determined with a pH measuring instrument, etc. The experimental results showed that 1-galloyl-glucose was the smoothest at 5°C among the three storage temperature conditions. It fluctuates and decreases in a curve at 35°C and 25°C. The content changes of gallic acid (GA) fluctuated more obviously at 35°C, and it showed a maximum value on the 7th day. The content changes of 1, 3, 6-tri-O-galloyl- β -D-glucose (TGG) all showed a peak on the 5th day and then showed a gradual decrease. The content changes of ellagic acid (EA) fluctuated more at 35°C. The peak of the content of rutin at both 35°C and 25°C appeared on the 3rd day, and that showed a gradually decreasing trend. The PPO activity varied more significantly at 25°C and 35°C. The browning index increased with time at both 35°C and 25°C. The complete browning of P. emblica was already observed on the 13th day. Tips for experimental results 5°C are effective in preventing browning of P. emblica. The contents of TGG, 1-galloyl-glucose, and rutin in P. emblica are greatly affected by temperature and time, and its contents had a linear relationship with time and temperature and can be used as one of the indicators of early browning, which provides a reference for the storage and transportation of fresh fruit in Chinese herbals.